The I-search paper - Macrorie, Ken, 1918-2009.; Macrorie, Ken, 1918-2009. (Portsmouth, NH : Boynton/Cook Publishers, Heinemann, 1988)
Synopsis: This revised and retitled edition of Searching Writing includes two additional I-Search papers, one by a teacher, and a new chapter entitled "The Larger Context," which shows how the I Search concept can work throughout the whole curriculum in school and college.
Part 1: Writing Every Day -- 1: Free writing -- 2: Loopy learning -- 3: Throwing back the engfish -- 4: Truthtelling -- 5: Cutting wasted words -- Part 2: I-Searching -- 6: I-Search paper -- 7: Topic choosing you -- 8: Locating sources -- 9: Tell it as story -- 10: Talking animals -- 11: Interviewing -- 12: I and the others -- 13: Objectivity and subjectivity -- 14: Five I-Search papers -- Part 3: Becoming An Editor -- 15: Bad words -- 16: Getting the point -- 17: Editing day -- Part 4: Looking In The cupboard -- 18: Filled with books -- 19: Issued periodically -- 20: Profundity of learning? -- 21: Sam and Noah -- 22: Historical lexicography -- 23: Spellynge, spellyng, spelling -- 24: Can I become a writer? -- 25: Larger context -- Suggestions for teachers -- List of sources -- Index.
"Revised edition of Searching writing."
Includes bibliography: p. 351-354 and index.
Also issued online.
Keywords: English language -- Rhetoric; Report writing; First person narrative